EXe-Learning Integration in Quran–Hadith Instruction: A Qualitative Study on the Shift from Behaviorist to Constructivist Learning in Madrasahs - Hamdi, Hamdi; Jasiah, Jasiah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This study aims to examine the use of eXe-Learning in Quran Hadith instruction, with a focus on the integration of relevant educational theories in supporting a shift in learning paradigms. A descriptive qualitative approach was employed. The research participants included teachers and students involved in Quran Hadith learning, particularly on the topic of Mad Thabi‘i. Data were collected through observations, interviews, and documentation. Data analysis followed the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the use of eXe-Learning reflects a transition in instructional approaches from teacher-centered (behaviorist) to learner-centered (constructivist) learning. The interactive modules developed through eXe-Learning assist students in understanding the concept of mad asli, recognizing the letters of mad, and accurately distinguishing vowel length, while also encouraging active engagement in the learning process. The implications of this study suggest that eXe-Learning can serve as an alternative digital learning medium in Quran Hadith subjects to support learner-centered instruction and to encourage teachers to integrate constructivist approaches in the design and implementation of learning activities that align with students’ characteristics in the digital era.